Long-Term m5C Methylome Dynamics Parallel Phenotypic Adaptation in the Cyanobacterium Trichodesmium. (6th October 2020) - Walworth, Nathan G; Lee, Michael D; Dolzhenko, Egor; Fu, Fei-Xue; Smith, Andrew D; Webb, Eric A; Hutchins, David A
Abstract: A major challenge in modern biology is understanding how the effects of short-term biological responses influence long-term evolutionary adaptation, defined as a genetically determined increase in fitness to novel environments. This is particularly important in globally important microbes experiencing rapid global change, due to their influence on food webs, biogeochemical cycles, and climate. Epigenetic modifications like methylation have been demonstrated to influence short-term plastic responses, which ultimately impact long-term adaptive responses to environmental change. However, there remains a paucity of empirical research examining long-term methylation dynamics during environmental adaptation in nonmodel, ecologically important microbes. Here, we show the first empirical evidence in a marine prokaryote for long-term m5C methylome modifications correlated with phenotypic adaptation to CO2, using a 7-year evolution experiment (1, 000+ generations) with the biogeochemically important marine cyanobacterium Trichodesmium . We identify m5C methylated sites that rapidly changed in response to high (750 µatm) CO2 exposure and were maintained for at least 4.5 years of CO2 selection. After 7 years of CO2 selection, however, m5C methylation levels that initially responded to high-CO2 returned to ancestral, ambient CO2 levels. Concurrently, high-CO2 adapted growth and N2 fixation rates remained significantly higher than those of ambient CO2 adapted cell lines irrespective of CO2 concentration, a trend consistent with genetic assimilation theory. These data demonstrate the maintenance of CO2 -responsive m5C methylation for 4.5 years alongside phenotypic adaptation before returning to ancestral methylation levels. These observations in a globally distributed marine prokaryote provide critical evolutionary insights into biogeochemically important traits under global change.